Effects of increasing and decreasing physiological arousal on anticipation timing performance during competition and practice. Issue 1 (2nd January 2016) - Duncan, Michael J.; Smith, Mike; Bryant, Elizabeth; Eyre, Emma; Cook, Kathryn; Hankey, Joanne; Tallis, Jason; Clarke, Neil; Jones, Marc V.
Abstract: The aim of this study was to investigate if the effects of changes in physiological arousal on timing performance can be accurately predicted by the catastrophe model. Eighteen young adults (8 males, 10 females) volunteered to participate in the study following ethical approval. After familiarisation, coincidence anticipation was measured using the Bassin Anticipation Timer under four incremental exercise conditions: Increasing exercise intensity and low cognitive anxiety, increasing exercise intensity and high cognitive anxiety, decreasing exercise intensity and low cognitive anxiety and decreasing exercise intensity and high cognitive anxiety. Incremental exercise was performed on a treadmill at intensities of 30%, 50%, 70% and 90% heart rate reserve (HRR) respectively. Ratings of cognitive anxiety were taken at each intensity using the Mental Readiness Form 3 (MRF3) followed by performance of coincidence anticipation trials at speeds of 3 and 8 mph. Results indicated significant condition × intensity interactions for absolute error (AE; p = .0001) and MRF cognitive anxiety intensity scores ( p = .05). Post hoc analysis indicated that there were no statistically significant differences in AE across exercise intensities in low–cognitive anxiety conditions. In high–cognitive anxiety conditions, timing performance AE was significantly poorer and cognitive anxiety higher at 90% HRR, compared to the other exercise intensities. There was no difference in timing responses at 90% HRR during competitive trials, irrespective of whether exercise intensity was increasing or decreasing. This study suggests that anticipation timing performance is negatively affected when physiological arousal and cognitive anxiety are high.